2014
DOI: 10.5009/gnl.2014.8.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure from Abdominal Imaging Studies in Patients with Intestinal Behçet Disease

Abstract: Background/AimsRecently, several studies have revealed that diagnostic imaging can result in exposure to harmful levels of ionizing radiation in inflammatory bowel disease patients. However, the extent of radiation exposure in intestinal Behcet disease (BD) patients has not been documented. The aim of this study was to estimate the radiation exposure from abdominal imaging studies in intestinal BD patients.MethodsPatients with a diagnosis of intestinal BD established between January 1990 and March 2012 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Several studies have recently demonstrated that patients with intestinal BD are exposed to high levels of radiation owing to an excessive use of abdominal CT scans [1]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have recently demonstrated that patients with intestinal BD are exposed to high levels of radiation owing to an excessive use of abdominal CT scans [1]. …”
Section: Discussionmentioning
confidence: 99%
“…Imaging of intestinal BD has been hindered for many years by the inherent limitations of the radiological techniques used to study the small bowel. In fact, only wireless capsule endoscopy and CT have been able to adequately image the gastrointestinal involvement of BD up to now [ 1 , 2 ]. MR-Enterography (MRE) is a relatively new imaging technique, which has already demonstrated a good diagnostic value for small bowel pathology, particularly in CD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Because GI involvement can cause severe morbidity and mortality, BD is designated “intestinal BD” if GI symptoms predominate and typical ulcerative GI lesions are objectively documented. 2 – 4 The frequency of GI involvement ranges from 3% to 50% and varies depending on geographic location. 5 , 6 The most frequently affected site is the ileocecal region, which presents with symptoms of abdominal pain, diarrhea, and bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…The first study to elucidate the cumulative radiation dose in patients with Behçet disease showed that a substantial proportion of intestinal Behçet disease patients were exposed to high doses of ionizing radiation from diagnostic tests, contrary to expectations 10. Over a mean follow-up of 7.5 years, 28.1% of intestinal Behçet disease patients received cumulative doses exceeding 50 mSv, with the mean dose being 41.3 mSv.…”
mentioning
confidence: 99%